John Steinbeck in Poland - Piotr Baracz:::Creator::::::::::::
Jonh Steinbeck stands and looks up at Hitler's Fuhrerhauptquartier Wolfsschanze in the Kraina Tysiaca Jezior region, Hitler's base for Operation Barbarossa and where an attempted assassination took place in 1944. Original in safe